Optimising pharmacotherapy for secondary prevention of non‐invasively managed acute coronary syndrome. (17th November 2014) - Thompson, Peter L; Thompson, Angus G; Judkins, Chris
Summary: About half of all patients who experience an acute coronary syndrome (ACS) in Australia have their conditions managed non‐invasively — that is, they do not undergo coronary angiography and revascularisation in hospital. ACS patients whose conditions are managed non‐invasively may not receive the same level of evidence‐based care as those who receive coronary revascularisation. This article reviews the optimal pharmacological management of ACS managed non‐invasively. There is strong evidence to support the prescription of dual antiplatelet therapy (DAPT; aspirin with a P2Y12 inhibitor). DAPT should continue for 12 months after an ACS, then aspirin should be continued indefinitely. Anticoagulation with warfarin or a novel oral anticoagulant may be needed if atrial fibrillation occurs; the combination with DAPT increases the risk of bleeding. Unless contraindicated, high‐intensity statin therapy should be prescribed for all post‐ACS patients irrespective of their cholesterol level. Non‐statin lipid therapy has not been shown to improve outcomes. Use of β‐adrenergic blockers is recommended in most guidelines, but the clinical trials to support this recommendation were performed more than 30 years ago, and routine long‐term use may not be relevant to modern treatment, except when there is cardiac failure or left ventricular dysfunction. Angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers are also widely recommended, but the evidence for benefit is stronger when there is left ventricular dysfunction. Calcium‐channel blockers, nitrates, antiarrhythmic drugs, digoxin and diuretics do not improve outcomes in post‐ACS patients.